Late Quaternary evolution of a lowland anastomosing river system: Geological-topographic inheritance, non-uniformity and implications for biodiversity and management. (15th May 2021) - Brown, Antony G.; Rhodes, Edward J.; Davis, Steve; Zhang, Yusheng; Pears, Ben; Whitehouse, Nicki J.; Bradley, Chris; Bennett, Jenny; Schwenninger, Jean-Luc; Firth, Antony; Firth, Emma; Hughes, Paul; et al.
Abstract: Lowland multiple-channel rivers are characterised by floodplain-corridor heterogeneity, high ecological and heritage value, and can be in quasi-stable states. This holistic study of a surviving temperate zone example (Culm, UK) uses geomorphological mapping, 14 C, direct sediment dating (OSL, fallout radionuclides), and palaeoecology. This reveals the evolution of a channel-floodplain system from an initial braided state in the Late Pleistocene to its late Holocene anastomosing state. After the Pleistocene-Holocene transition the reduced channel system incised into its braid-plain, only able to rework gravels locally due to reduced competence in relation to inherited bounding sediment calibre. This resulted in the creation of terrace islands, palaeochannels, and a stable anastomosing pattern dominated by channel junctions, bifurcations and palaeochannel intersections. Survey, coring and excavation reveal a persistence of mid-channel bars and riffles at channel junctions, and where channels crossed palaeochannel fills. In common with most other European lowland rivers this system evolves in the later Holocene due to both climate and catchment changes with a major hydrological critical transition in the mid-Holocene (c. 5300 BP). However, in the case of the Culm, the increase in fine sediment supply often seen in lowland catchments in the Middle-Late Holocene, occurred later, and was insufficient to convert the system to a single medium-low sinuosity channel-floodplain. This allowed the persistence of high heterogeneity and biodiversity (including the persistence of riffle beetles) as part of multiple-scales of non-uniformity. Indeed the pool-riffle persistence is an example of this system's non-uniformity, being due, at least in part, to the effects of previous channel history. This paper reveals why this river survived in a multichannel state, and by implication, why others did not. These results are being used in the bespoke eco-heritage management of the Culm, but could also inform the restoration of other former multi-channel lowland temperate river systems worldwide. Highlights: Anastomosing channel system in SW England in quasi-equilibrium due to co-occurrence of inherited boundary conditions with dynamic fluvial processes. Temporal pattern of channel abandonments reflects climate late-Holocene climate change and late rise in fine-sediment supply. Simple catchment model suggests that mid Holocene low discharge promoted lack of channel change and sedimentation. Some riffles/mid channel bars formed by fluvial response to inherited floodplain features. Persistence of complex channel pattern promoted high biodiversity including persistence of riffle beetle species.